(untitled) (Journal of Studies in History and Archeology, 2023)
Sufism is one of the symbols of the ritual acts that have accompanied the life of humanity since the beginnings of the heavenly religions. Muslim Sufis have taken from those symbols mentioned in the Bible in the Gospel of John from them, the light and divine love and the state of conscience that befalls the walker when he reaches divine love, and sacrifice, and water that is the basis The existence of life. Thus, it appears that the symbols of Sufism are shared by Sufis through the stages of human life, and the Gospel of John referred to them in detail through the biography of the life of our master Christ (peace be upon him).